Produções científicas do Congresso Brasileiro de Educação Especial (CBEE) no eixo educação física e esportes adaptados, de 2014 a 2018 - SOUSA, Felipe Ramos de (2022)
This study was conducted with the aim of analyzing the scientific production of the Brazilian Congress of Special Education – CBEE, in the period from 2014 to 2018, within the Axis Physical Education and Adapted Sports. The methodology uses the qualitative approach, through the elaboration of a state of the art. The results indicate that the productions are configured in the following 5 thematic categories: teaching-learning methodologies, body culture practices, teacher training, literature reviews and social practices, in which it is possible to perceive the importance of basing Physical Education in inclusive ways and also allows to visualize the difficulties encountered in the field researched from the categories found. In the meantime, we consider that the productions have been elucidating how the training of Physical Education teachers in an inclusive perspective contributes to the improvement of the teacher himself as a professional, enabling greater accessibility of people with and without disabilities to body practices, and consequently to the development of these students.